الأسماء والصفات عند الشيخ أحمد بن اسماعيل الگوراني الكوردي- عرض ونقد البحث مستل من أطرحة دكتوراه - كريم, عبدالله محمد; محمد, نوزاد إبراهيم (Sulaimani Journal for Humanities, 2023)
Knowledge of the names of God Almighty and His sublime attributes opens the door for the servant to know the Lord, the Blessed and Most High. Since the basis of correct knowledge is belief in God and His names and attributes, this type of faith is the life of the hearts. Knowing the Names and Attributes is the greatest way to know God and His attributes of perfection and majesty. Being studying and analyzing a vital topic of faith. Contributing to the service of the Islamic faith by clarifying and explaining the verses of the names and attributes in the Holy Qur’an and its contribution to serving the students of knowledge. Love, desire and impulsiveness to serve the Islamic faith. Obtaining the reward from God Almighty, asking the Lord for repayment and sincerity.